DANCE PERFORMANCE TO ACHIEVE MURI: STUDY OF REJANG SANDAT RATU SEGARA DANCE PERFORMANCE IN TANAH LOT, TABANAN, BALI - Putri Negara, Ni Made Ari Yanti; Darma Putra, I Nyoman; Arjani, Ni Luh (E-Journal of Cultural Studies; Vol 15 No 3 (2022): Volume 15, Number 3, August 2022DO - 10.24843/cs.2022.v15.i03.p01, 2022)
Rejang is a sacred dance that has certain standards in its creation and performance. This sacred dance is performed during the Dewa Yadnya ceremony by taking into account the place, time, and means of offerings that have been determined. However, recently a new creation of Rejang dance has emerged which has a function not for religious ceremonies, but for other purposes such as entertainment to achieve a MURI (Indonesian Record Museum) record. This type of Rejang Dance is the Rejang Sandat Ratu Segara Dance which was staged on August 18, 2018 in Tanah Lot, Tabanan, Bali. This certainly attracts the attention of the people of Tabanan and causes this dance to be widely discussed on social media and in real life. This article examines the form of the Rejang Sandat Ratu Segara Dance and finds out how it differs from the Rejang dance in Bali. The research method used is qualitative research with descriptive and explanatory exposure. In this study, there are several differences in the form of the Rejang Sandat Ratu Segara dance with the Rejang dance that developed in Bali such as movement, dancers, clothing, and settings. Keywords: Rejang Sandat Ratu Segara Dance, Tanah Lot Tabanan, MURI record, sacred art